Metabolic Syndrome and its Components Among Patients Attending MOPD of A Tertiary Care Centre - Khan, MM Rahman; Chowdhury, MAJ; Haque, MZ; Chowdhury, MMH; Rahman, MK; Rashid, MH; Mahmood, I; lslam, QT (TAJ: Journal of Teachers Association, 2009)
This was a hospital based study done on 334 patients attending in medicine OPD BSMMU. According to modified NCEP ATP Ill criteria 27.2% of subjects aged 20 years had the metabolic syndrome and was more commonly seen in women than in men (32.4% vs 21.7%, P<0.05). The metabolic syndrome increased with age in both sexes (40-49 years age groups 24.2% to 50-59 years age groups 35.2%). Majority of the patients (59.3%) were in the age group 40-60 years. Overall frequencies of components of the metabolic syndrome were in the order of abdominal obesity (97.8%) > low high density lipoprotein (83.5%) > hypertension (71.4%) > triglycerides (67.0%) > fasting plasma glucose (44.0%). Abdominal obesity appeared to be the highest frequent components of the metabolic syndrome in both sexes (men 100% and women 96.4%). However, among male patients, high serum triglycerides (77.1%) appeared to be the second frequent components. Whereas among female patients low high density lipoprotein cholesterol (96.4%) appeared to be the second frequent component and was found to be high compared to the male patients (62.9%). Most of those with metabolic syndrome had three components of the syndrome (48.3%), 38.4% had four, and 13% had five components. The percentage of clusters of components increased with age of the patients and in female sex. TAJ 2009; 22(1): 176-182